Role of Tenecteplase in management of acute ischemic stroke: a knowledge, attitude, and practice survey among Indian neurologists - Jadhav, Amit Y.; Dhediya, Rajnish M.; Swami, Onkar C. (International Journal of Research in Medical Sciences, 2021)
Background: Tenecteplase, a third generation tissue plasminogen activator has important place in the thrombolytic therapy in acute ischemic stroke. The objective of present study was to understand the knowledge, attitude and practice (KAP) towards the usage of tenecteplase in daily clinical practice. Methods: This was a prospective questionnaire based knowledge, attitude and practice survey with involvement of practising neurologists across the country. A specially designed validated questionnaire containing 18 questions was shared with neurologists and their anonymous inputs were captured and analysed in qualitative manner. Results: Total Sixty-eight neurologists completed this questionnaire. The 73 percent of neurologist preferred tenecteplase in stroke patients arriving within 4.5 hours of onset of stroke symptoms. Almost 70% of neurologists preferred tenecteplase in patients <60 years of age with average NIHSS score between 5-15. The preferred dosage was 0.2 mg/kg by majority (78%). Bridging therapy was used up to 0-10% of patients by 70% neurologists which ultimately has lesser bleeding chances. 46% neurologists reported that no sICH after tenecteplase, while 30% reported in <1% patients. Almost 70% neurologists reported no allergic reaction noted with tenecteplase. Overall, 70% neurologists reported good to very good improvement in the patient’s quality of life at 90 days after tenecteplase therapy. Conclusions: The current KAP survey emphasized tenecteplase as a commonly preferred thrombolytic agent in acute ischemic stroke with better efficacy and safety, affordable cost with single bolus administration.